Remote medical care monitoring system - Alsaraira, Amer; Alabed, Samer; Saraereh, Omar (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Neglecting one's health is a major contributor to the decline in overall well-being, often resulting in the onset of various diseases and health issues. The avoidance of such complications becomes feasible with the introduction of a device capable of monitoring heart pulses at regular intervals, ideally every 60 seconds. The main goal of this article is to design a healthcare system that ensures continuous monitoring of heart activity and temperature, functioning as a proactive tool to keep individuals informed about their physiological parameters. This involves the incorporation of a heart rate sensor and temperature sensor in a wearable device, essentially serving as a first aid tool. The heart rate is measured by detecting pulses and calculating beats per minute, utilizing an appropriate heart monitoring sensor tailored to the specific needs of the individual. The main concept revolves around designing a wearable device that harnesses the capabilities of the digital age, making use of features such as wireless sensors and rapid data transfer through the internet of things, accessible on various smart devices. The device focuses on detecting and monitoring heart rate and temperature, with the sent data being relayed to the healthcare provider. The doctor can then monitor the patient's status through the displayed data on thing-speak.